Path Analysis on The Biological and Social Life Course Factors Affecting Childs Speech and Language Development Delay - Indriasih, Merlita; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2019)
Background: The development in children occurs once during the period of their life. The language ability is an indicator of all the development. The lack of stimulation can cause speech and language disorders and this disorder can persist. This study aimed to determine the effects of biological and social life course factors on delayed speech and language development.Subjects and Method: This study was an observational analytic with cross-sectional approach, conducted in 25 integrated health posts (posyandu) located in Sleman Regency, Yogyakarta in March to April 2019. The total sample of 225 toddlers was chosen using fixed exposure sampling. The dependent variable was delayed speech and language development. The independent variables were income, employment, nutritional status, birth weight, history of toxoplasma, rubella, CMV and TORCH, history of infection, duration of gadget use, language, frequency of posyandu visit, and early childhood education (PAUD). Data collection on delayed speech and language development were measured by Denver II. The data were analyzed by path analysis.Results: Speech and language delayed development was directly decreased with normal birth weight (b= -2.19; 95% CI= -3.58 to -0.79; p= 0.002), employed mother (b = -1.32; 95% CI = -2.38 to -0.27; p = 0.013), good nutritional status (b = -2.14; 95% CI = -3.37 to -0.91; p = 0.001), regularly attend integrated health post (b = -1.29; 95% CI = -2.31 to -0.26; p = 0.013 ), mono language (b = -1.02; 95% CI = -1.99 to -0.04; p = 0.041), low duration of gadget use (b = -1.59; 95% CI = 0.23 to 2.33; p = 0.017). Speech and language delayed development was directly increased with history of disease (b = 1.37; 95% CI = 0.34 to 2.40; p= 0.009), and did not attend Pre-school (b = 1.28; 95% CI = -2.65 to -0.53; p = 0.003). It was indirectly affected by number of children, income, and history of TORCH.Conclusion: Delays in speech and language development are directly influenced by birth weight, infection history, employment, nutritional status, frequency to posyandu (integrated health posts), long usage of gadgets, PAUD (pre-school) and indirectly influenced by income and the number of children.Keywords: the development of speech and language, the use of gadgetsCorrespondence: Merlita Indriasih. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir.Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: merlitaindriasih@gmail.com. Mobile: 085641097941.Journal of Maternal and Child Health (2019), 4(6): 11-22https://doi.org/10.26911/thejmch.2019.04.06.02